Effects of intensity and modality of community-based exercise programs on mood profile and functional physical capacity in older women under socioeconomic vulnerability: A randomized trial - Zanini, Gabriel de Souza [UNESP]; Amaral, Vanessa Teixeira do [UNESP]; Fernandes, Bianca [UNESP]; Verardi, Carlos Eduardo Lopes [UNESP]; Ciolac, Emmanuel Gomes [UNESP] (SAGE Publications, 2025)
BACKGROUND: The prevalence of mood disorders and functional decline among older adults, particularly those under socioeconomic vulnerability, has become a significant public health concern. Physical exercise is widely recognized as a key intervention for improving both physical and mental health in older populations. However, the optimal intensity and modality of exercise for enhancing mood and functional capacity in older women under socioeconomic vulnerability remain unclear. OBJECTIVES: To investigate the effects of the intensity and modality of community-based exercise programs on mood profile and physical functional capacity in older women under socioeconomic vulnerability. DESIGN: This article presents a prospective, randomized, single-blind study. METHODS: Older women under socioeconomic vulnerability (included: n = 116; lost to follow-up: n = 28; analyzed: n = 88) were randomly assigned to 6 months of high-intensity interval training combined with resistance training (n = 25), moderate-intensity continuous training combined with resistance training (n = 37), or resistance training (n = 26) interventions performed twice weekly. Flexibility (seat and reach), handgrip strength, lower limb muscle strength/power (Five-Time Sit-to-Stand), mobility (Timed Up and Go), aerobic performance (6-min walking), and mood profile (Brunel Mood Scale) were assessed before and during follow-up. RESULTS: All groups had improved (p < 0.05) Five-Time Sit-to-Stand and 6-min walking performance, while high-intensity interval training combined with resistance training and resistance training improved (p < 0.05) Timed Up and Go performance. There were also significant improvements (p < 0.05) in depression (high-intensity interval training combined with resistance training and moderate-intensity continuous training combined with resistance training), anger (resistance training), vigor (high-intensity interval training combined with resistance training and moderate-intensity continuous training combined with resistance training), fatigue (resistance training), confusion (moderate-intensity continuous training combined with resistance training), and total mood disturbance (high-intensity interval training combined with resistance training, moderate-intensity continuous training combined with resistance training, and resistance training). CONCLUSION: Six months of community-based exercise was effective for improving functional physical capacity and mood profile in older women under socioeconomic vulnerability, regardless of exercise intensity or modality. CLINICAL TRIAL REGISTRATION: RBR-3y8w4w3.